Sodium Dichloroacetate Stimulates Angiogenesis by Improving Endothelial Precursor Cell Function in an AKT/GSK-3β/Nrf2 Dependent Pathway in Vascular Dementia Rats - Zhao, Hui; Mao, Junqin; Yuan, Yuan; Feng, Jingjing; Cheng, Hao; Fan, Guorong; Zhang, Yuefan; Li, Tiejun (Frontiers in Pharmacology, 2019)
Sodium dichloroacetate (DCA) is a mitochondrial pyruvate dehydrogenase kinase inhibitor, and has been shown to display vasoprotective effects in chronic ischemic stroke. The purpose of this study was to evaluate the therapeutic effect of DCA on vascular dementia and endothelial progenitor cell (EPC)-mediated angiogenesis. After cerebral ischemia-reperfusion in rats, DCA was administered continuously for 21 days; following which, histological analysis and cognitive functional tests were conducted. Rat bone marrow-derived endothelial progenitor cells (EPCs) were isolated, their function and quantity were measured, and the effects of long-term administration of DCA on EPCs in a rat model of vascular dementia (VD) was studied. We found that long-term DCA administration improved cognitive function in VD rats, reduced brain infarct size and brain atrophy，increased VEGF and bFGF levels in vivo, promoted angiogenesis in damaged areas, and significantly improved EPC function in VD rats. Compared with the VD group, AKT, Nrf2, eNOS expression, and intracellular NO levels were elevated in EPCs of DCA-treated VD rats. In addition, GSK3β and intracellular ROS levels were decreased. Simultaneously, it was found that DCA directly acted on EPCs, and improved EPC functional behavior. Taken together, these findings suggested that long-term DCA administration improved cognitive function in a rat model of vascular dementia, and did so in part, by improving EPC function. Observations suggest that prolonged DCA administration might be beneficial in treating vascular dementia.